The Role of Media and the Effectiveness of Influencer Marketing on Customer Behavior in Digital Business - Raynaffan Prasadja; Abdul Khalid Al-Mubarak Dalimunthe; Achmad Farhan Prasojo; Mokhamad Mirza Rizky Sahara (Universitas Negeri Surabaya, 2026)
This study examines the influence of Digital Media Role and InfluencerMarketing on Consumer Behavior within the context of TikTok, one of themost prominent short-video platforms shaping contemporary digitalconsumption patterns. Using a quantitative approach, data were generatedfrom 150 respondents to analyze how TikTok’s algorithmic features andinfluencer credibility jointly affect user decision-making. Reliability andvalidity analyses confirmed strong internal consistency across allconstructs. Descriptive results indicated generally positive perceptionstoward TikTok’s media affordances and influencer content. Regressionanalysis revealed that both Digital Media Role (X1) and Influencer Marketing(X2) significantly and positively influenced Consumer Behavior (Y),explaining 40% of the variance in behavioral outcomes. The balanced effectsizes indicate that platform-level stimuli and influencer-driven cuescontribute equally to shaping user responses. These findings support thetheoretical assumptions of the Stimulus–Organism–Response (S-O-R)framework and align with the AIDA model, highlighting how attention,perceived relevance, and credibility collectively drive behavioralengagement. This study contributes to the growing body of digital marketingliterature by demonstrating the dual-channel persuasion mechanisminherent in TikTok’s environment. Practical implications suggest that brandsshould optimize both algorithmic visibility and influencer partnerships toeffectively influence consumer behavior. Future research may include